Severe burn injuries: the say the sodium starts rising - Menger, Maximilian M.; Wenz, Holger; Bamberg, Maximilian; Krauß, Sabrina; Lauer, Henrik; Viergutz, Tim; Fontana, Johann (In vivo, 2024)
Background/Aim: The current study was designed to evaluate the etiologies of hypernatremic episodes in patients with severe burn injuries in comparison to critically ill non-burn patients. Patients and Methods: The retrospective data acquisition was limited to the first 14 days and to patients with at least 20% total body surface area (TBSA) 2nd degree burn injuries or more than 10% TBSA when including areas of 3rd degree burn injuries. The results were compared to the results of a previously published study that analyzed the risk factors for hypernatremia in 390 non-burn intensive care unit patients. Results: In total, 120 patients with a total of 50 hypernatremic episodes were included. Compared to non-burn injury patients, no significant differences were detectable except for a lower rate of hypokalemia and a higher rate of mechanical ventilation. The main trigger for hypernatremic episodes was the loss of free water, while 24% of the hypernatremic episodes seemed to be at least partly triggered by a surplus sodium influx. Patients with hypernatremic episodes had a significantly higher mortality rate. However, in none of the cases was hypernatremia the decisive cause of death. Conclusion: Besides the unique phenomenon of high volume internal and external volume shifts, the overall risk factors and etiologies of hypernatremia in patients with severe burn injury do not seem to significantly differ from other ICU patient collectives. Remarkably, a surplus of sodium influx and therefore a modifiable factor besides the specific burn injury volume resuscitation had an impact on the hypernatremic episodes in 24% of cases.